2022
DOI: 10.1007/s00167-022-06892-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound shear wave elastography-derived tissue stiffness is positively correlated with rotator cuff tear size and muscular degeneration

Abstract: PurposeThe purpose of this study is to describe rotator cuff muscle stiffness in patients with different degrees of rotator cuff tear (RCT) severity and to assess its predictive ability for RCT reparability. MethodsOne hundred and thirty‐three consecutive patients who were scheduled to undergo arthroscopic shoulder surgery were prospectively enrolled. Tendon retraction, fatty infiltration, and muscle atrophy were evaluated using magnetic resonance imaging. Shear modulus of supraspinatus (SSP) and infraspinatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Eight studies utilized SWE to compare quantitative characteristics of the rotator cuff and correlated the findings with MRI, with conflicting results. Huang et al found that SWE-derived rotator cuff muscle stiffness is highly correlated with rotator cuff tear size and severity [ 40 ]. In addition, shear modulus values of supraspinatus and infraspinatus muscles among affected shoulders were significantly stiffer than the values in the contralateral normal shoulder.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies utilized SWE to compare quantitative characteristics of the rotator cuff and correlated the findings with MRI, with conflicting results. Huang et al found that SWE-derived rotator cuff muscle stiffness is highly correlated with rotator cuff tear size and severity [ 40 ]. In addition, shear modulus values of supraspinatus and infraspinatus muscles among affected shoulders were significantly stiffer than the values in the contralateral normal shoulder.…”
Section: Resultsmentioning
confidence: 99%